Bentuk Impresi/Kandoushi Maskulinitas dan Feminitas dalam Anime Kimi no Na wa - Indrowaty, Sri Aju; A.B Cahyono; F.E. Rahmawati; S. D. Febrianda; D.N. Latifah (Universitas Negeri Jakarta, 2025)
Language is something that cannot be separated when socializing with others, and it adapts not only to the origin of language, but also to ethnic origin, social status and gender (Dor et al., 2014). This research will discuss the types and meanings of kandoushi in masculinity and femininity in the anime Kimi no na wa with the aim of explaining the types and meanings of kandoushi in anime. This study uses a qualitative method by using secondary data sources taken from the recording and listening techniques. This research uses theories taken from Iwabuchi and Terada Takanao. The data source used in this study is the dialogue and situation in the anime